2020
DOI: 10.1371/journal.pone.0233606
|View full text |Cite
|
Sign up to set email alerts
|

Local and national stakeholders’ perceptions towards implementing and scaling up HIV self-testing and secondary distribution of HIV self-testing by Option B+ patients as an assisted partner service strategy to reach men in Haiti

Abstract: HIV self-testing (HIVST), which allows people to test in private, is an innovative testing strategy that has been shown to increase HIV testing among men. Delivering HIVST kits to men via women is one promising assisted partner service strategy. Little research has been conducted on HIVST secondary distribution to men by women living with HIV (WLWH) in the Caribbean and other settings. The purpose of this study was to assess the perspectives of WLWH, their male partners, and healthcare professionals on the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…However, secondary distribution to partners has been carried out successfully in the context of couple testing, health workers ( 43 , 44 ) and among MSM ( 45 , 46 ). Gender norms and power imbalances could negatively impact the ability of a woman to propose HIVST to her male partner, as mentioned in our study regarding FSW and as observed in other studies among pregnant women ( 33 ). Providing tips to primary contacts so that they have the necessary capacity to inform, negotiate and offer the HIVST kit remains essential for secondary distribution.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, secondary distribution to partners has been carried out successfully in the context of couple testing, health workers ( 43 , 44 ) and among MSM ( 45 , 46 ). Gender norms and power imbalances could negatively impact the ability of a woman to propose HIVST to her male partner, as mentioned in our study regarding FSW and as observed in other studies among pregnant women ( 33 ). Providing tips to primary contacts so that they have the necessary capacity to inform, negotiate and offer the HIVST kit remains essential for secondary distribution.…”
Section: Discussionsupporting
confidence: 73%
“…In the context of high stigmatization of key populations, doubts about their willingness to connect with care were found in this study. Connecting with confirmatory and care services following a reactive HIVST result is perceived as a challenge in almost all studies ( 24 , 27 , 33 , 34 ). However, according to the WHO, people who used HIVST have the same link-to-care practices as those tested with providers' support ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all studies concluded that HIV-ST was perceived easy to use [23, 28, 30-32, 35, 38, 40, 42, 44, 46, 47, 49, 57, 61, 63, 68, 70, 74, 77, 80, 82, 83, 85, 127, 130-134, 141]. Most studies 107,113,114,119,121,[183][184][185][186][187][188][189][190] and six observational mixed method studies [126,129,136,138,191,192]. While adoption is distinct from appropriateness, we found that qualitative results for adoption overlapped with results for appropriateness and we opted to report them together (with acceptability) in the next section.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Partner distribution is an often-used strategy for distributing HIV-ST kits. Several papers explored issues of acceptability and appropriateness [94, 95, 99-102, 105, 107, 114, 118, 119, 121, 122, 127, 183, 184, 186, 189, 191, 196] and all except one [121] were done in African countries. Female partners find this strategy acceptable because it allows them to engage their partners in matters of sexual health and see it as a good way to encourage HIV testing and even couple testing (testing at the same time).…”
Section: Positive Perceptions On Hiv-stmentioning
confidence: 99%
“…As a result from these studies, the World Health Organization (WHO) now recommends HIVST as one of the testing strategies for HIV prevention efforts (30). These studies, including our own (31)(32)(33)(34)(35)(36)(37)(38)(39), have provided evidence on different distribution strategies from online platforms, peers to sexual partners, community health workers (40)(41)(42). Similarly, these studies have assessed different approaches to verify HIVST results either through direct supervision by health provider, requesting participants to return used HIVST kits, electronic transmission of photographs, or using Bluetooth sensors (43).…”
Section: In-home Hiv Self-testing Historymentioning
confidence: 99%